LEGAL ISSUES PARTICIPATION OF THE PROSECUTOR IN ECONOMIC CASES (American Journal of Pedagogical and Educational Research, 2024)
The article examines the issues of prosecutor's participation in the economic process, forms of participation. The legislation of Western Europe and the USA on the participation of the prosecutor in court proceedings is analyzed. It is concluded that the prosecutor who filed a statement of claim (application) in the interests of a citizen and a legal entity does not have the right, if the plaintiff does not agree, to change the basis or subject of the claims made against him, to make additional claims, to increase or decrease the amount of the claim.